Estudo da metilação de DNA em genes relacionados às vias de sinalização da produção de citocinas na periodontite - Luiz Paulo Carvalho Rocha (2021)
Periodontitis is an immunoinflammatory disease characterized by the destruction of periodontal tissues in response to a periodontopathogenic challenge. The onset and progression of the disease are marked by cellular and molecular changes that lead to a pattern of non-resolving, destructive inflammatory responses. This pattern results in clinical findings such as greater probing depths and clinical attachment loss. The destructive inflammatory mechanisms of periodontitis present periods of activity and quiescence, and the cytokine production profile can define the duration of periods and determine the degree of periodontal damage. A change in the cytokine production profile can be regulated by the gene expression of several signaling molecules. Gene expression, in turn, can be altered by epigenetic modifications. DNA methylation is an epigenetic alteration that can decrease expression when present. The general objective of this work was to evaluate the presence of DNA methylation in genes related to the signaling pathway of cytokine production in gingival tissue fragments from individuals with periodontitis. This study included 60 patients, 30 healthy and 30 with periodontitis, matched for age and sex. Gingival tissues were collected from affected sites in patients with periodontitis and similar areas, without signs of inflammation and changes in the periodontium, in control patients. The samples were submitted to DNA and RNA extraction and later to a protocol for DNA methylation profile pattern identification using qPCR. We performed an initial assessment of the DNA methylation pattern of 22 genes in a pool of samples, and we observed four genes with a methylation difference more significant than 20% between the control and patient groups. Such genes, MALT1, LTB, STAT5A, and FOXP3, were selected for further analysis. We observed that the MALT1 and LTB genes presented differences between the groups (p = 0.05 and p = 0.04, respectively). The STAT5A gene showed lower methylation in the periodontitis group compared to the control group (p = 0.025). The FOXP3 gene showed a higher percentage of methylation in the periodontitis group than the control group considering men (p = 0.037) and lower levels of transcripts (p = 0.037). We concluded that changes in the methylation profile of the MALT1, LTB, STAT5A, and FOXP3 genes are present in the gingival tissues of patients with periodontitis. Hypermethylation and low transcription of FOXP3 may be related to the pathogenesis of the disease in men. Furthermore, STAT5A transcription appears to be related to the clinical parameters of the disease in women. Additional studies on these genes may contribute to a better understanding of the pathogenesis of the disease.